TABOO WORDS AND MORAL VALUE ANALYSIS IN “BAD TEACHER” MOVIE BY JAKE KASDAN - Marni Hasibuan (Universitas Indraprasta PGRI, 2018)
The purpose of this research is to analyze taboo words and moral value analysis in the “Bad Teacher” movie by Jake Kasdan. The method she used in this research is descriptive qualitative research that aims to describe taboo words and moral value contained in the movie “Bad Teacher”. The duration of the movie “Bad Teacher” is 92 minutes. The data obtained are to be analyzed and classified based on taboo words from the dialogue and the moral value, which consists of five elements, there are kind and friendly, bravery, honesty, hard work, honesty, and patriotism. 1) After analyzing the pragmatics and moral value from the movie Bad Teacher” by Jake Kasdan which consist of 52 dialogues, the writer found out that there are 32 dialogues used taboo words and 2) 13 conversations contains moral value: 5 conversations or 38,48% moral value of kind and friendly, four conversations or 30,76% of hard work, two conversations or 15,38% of patriotism, one conversation or 7,69 of honesty, one conversation or 7,69% of bravery. Kind and friendly reached the most percentage because the consisting of life in the school from many kinds of characters, and it makes the story more exciting and touching.Keywords: sociolinguistics; moral value; taboo; movie analysis